Representações sociais de mulheres amazônidas sobre o exame papanicolau: implicações para a saúde da mulher - SILVA, Sílvio Éder Dias da (2014)
This research has as objective to describe the social representations of women amazônidas on the Papanicolau examination and to analyze the implications of this for the same care of itself. One is about a qualitative-exploratório study with the use of the Theory of the social representations. The collection of data was carried through in the period from January through December of 2007, with the use of two techniques: the interview half-structuralized with open questions and the free comment. For the interpretation of these data the technique of analysis of thematic content was used. The research had as a result, three thematic units, thus called: The Papanicolau examination - a care with the health of the woman; Taboos and beliefs on the Papanicolau examination; and practical One of same care of itself: the Papanicolau examination. In the study we observe that the women are afraid of having uterine neoplasm for this reason, the Papanicolau examination represents a practical care of itself.